NIHANSU-SAVAGE RISK FEATURE IN NO-PAIN PLAY WITH UNCERTAINTY - V. Zhukovskiy; L. Zhukovskaya (Вестник Северо-Кавказского федерального университета)
The article describes the peculiarities of Nihansu-Savage risks in game tasks. The first is related to the lack of unity of the Nash equilibrium situation in noncooperative games. In this case, it is proposed to follow such Nash equilibrium, which is simultaneously maximum by Slater. The second feature is the semantic content of the Nihans-Savage risk-determining win function (as the predicted and/or «desired» value of said function). The work considers the interaction ofplayers from the position ofpossible support (assistance) of some parties to the conflict by others.